THE USE OF PROJECTION AS LEARNING MEDIA OF SOCIOLOGY AT CLASS XI IPS IN SMAN 12 PADANG - Rahman, Abdul; Adiyalmon, Adiyalmon; Yasin, Faishal (Pendidikan Sosiologi, 2013)
The background of the problem on this research was using projection as learning media which is un-maximal used by some teachers in SMAN 12 Padang. The writer formulated the research question about what blocked and stimulated factors are used in projection media of sociology at class XI IPS SMAN 12 Padang. The aim of the research was to find out blocked and stimulated factors are used in projection media of sociology at class XI IPS SMAN 12 Padang.This research used qualitative method. Type of the research is descriptive. The subject of this research was sociology teachers and students of class XI IPS. The sources of this research consisted of primary data were collected by interview and observation, and secondary data were collected from school. The technique of collecting data was interview, observation, and documentation. The technique of analyzing data was collection of data, data reduction, display data, and conclusion.The result of the research showed that sociology teachers have used projection as learning media. However, it was not optimal used. 1) The stimulated factor of using projection were; a) increasing studentsâ interest and motivation in learning, b) Learning process became easy to understand and comprehended, c) Giving contribution to teacher and students in improving learning activity. 2) The blocked factor of using projection was; a) Limited projection, b) Teacher was uncreative in elaborating power-points and films.